Analisa Kendala serta Upaya dalam Pelaksanaan Pembinaan Fisik dan Mental Bagi Narapidana Anak di Lembaga Pemasyarakatan Khusus Anak Kelas I Blitar - Dinata, Qiandana Wisnu; Indawati, Yana (Hukum dan Masyarakat Madani, 2025)
This research aims to analyze the obstacles and efforts in implementing physical and mental development for child prisoners at the Blitar class I special children's correctional institution. The urgency of this research is to measure whether the implementation of physical and mental development for inmates at the Blitar special correctional institution for class I children is in accordance with the objectives of the correctional institution. The research method used by the author is empirical juridical. The results of this research show that there are obstacles in the form of facilities and infrastructure, limited abilities of officers and experts, budget limitations, and obstacles from target children who are less enthusiastic. Meanwhile, efforts that can be made to overcome these obstacles are by improving facilities and infrastructure, improving the limitations of officers and experts, increasing the budget, and encouraging the enthusiasm of the target children.   Keywords: Penitentiary, Children, Prisoners.